ANALISIS PENGEMBANGAN PRODUK RADIO KAYU MAGNO (Studi pada CV. Piranti Works Kecamatan Kandangan Kabupaten Temanggung) - Ferdiyan Imam Prihandono; Hari Susanta Nugraha; Agung Budiatmo (Universitas Diponegoro, 2016)
New Product Development activity which run by CV. Piranti Works on radio scope product had successfully create a brand new product through its Magno wooden radio. From this activity CV. Piranti Works is able to increase the acceptance of radio product in the middle of many other modern electronic products. The main point on this research that researcher is trying to find is how CV. Piranti Works runs the New Product Development activities that leads to creation of Magno wooden radio.The type of this research is descriptive qualitative study, this research is focused on New Product Development steps including ideas generate, prototyping, product test and evaluation steps. Data collection methods used in this research are interviews, observations and documents study. While the scope of this research is include whole divisions of CV. Piranti Works with the owner and its staff as the key informants.The result shows that four steps of New Product Development that run in making Magno wooden radio are all related and affect each other. There are differences between New Product Development which is run by CV. Piranti Works and the NPD Models, in which the New Product Development that run by CV. Piranti Works is focused on developing the value of the product besides intensifying the market, and as a social oriented product.The Conclusion of this research as CV. Piranti Works run its New Product Development activity is the creation of development method which is called “New Craft” method, while “Brand Story” method used as a promotion method using the principles of social marketing. There are several challenges that may comes, first is how can CV. Piranti Works keeps its product life cycle, second is how can this product and its story could be spread out more widely to the market. Hopefully that CV. Piranti Works could use a more modern technology to overcome obstacles in realizing the design, also optimizing the use of magno-radio.com website and relation with other media partners in term of communicating brand story and firm’s social activity.